Manipulating D–A interaction to achieve stable photoinduced organic radicals in triphenylphosphine crystals. Issue 7 (26th January 2023) - Tang, Chunlin; Song, Lijuan; Zhou, Kang; Ren, Peng; Zhao, Engui; He, Zikai
Abstract : Herein, we realized the quick generation of stable photoinduced radicals in donor–acceptor triarylphosphines with associated color changes of emission and absorption, which was deciphered by the electron paramagnetic resonance (EPR) spectra. Abstract : New strategies for the design and synthesis of stable organic radicals without additives are highly desirable. Herein, we design a series of donor–acceptor structured triarylphosphines and disclose the fast color change triggered by UV-irradiation in the crystalline state. Photoinduced organic radicals are undoubtedly verified and proved to be the reason for the color change by time-dependent and quantitative electron paramagnetic resonance analysis, X-ray crystallographic analysis, and theoretical calculations. It is revealed that the intrinsic symmetry breaking of peripheral architecture helps to form continuous molecular chains by donor–acceptor counterpart pairing. Intermolecular electron-transfer occurs among molecular chains and results in radical ion pairs upon photoirradiation.